DRE’S TRANSNATIONAL HEROIC JOURNEY IN HARALD ZWART’S THE KARATE KID MOVIE - QOWIY DIBYO PURUHITO (The English Department, Faculty of Languages and Arts, Universitas Negeri Surabaya, 2022)
Hero's journey exists in every story. According to Vogler, every character could be a hero in their own journey. Thus, this study is to analyze the Hero's journey in The Karate Kid movie. Instead of using Campbell's, this study uses Vogler's stages to reveal the heroic representation of Dre -the main character from the movie. The study also employs a critical approach on Dre's cross-cultural experience by using Hofstede's cultural values dimension theory to identify the discrepancy between his native and Chinese (his new) culture. The result of this study contains twelve stages of Hero's Journey proposed by Vogler as well as Dre's challenge on his personal growth. Moreover, cultural values dimension took major part on supporting his journey to achieve his goals. Keywords: cross culture, hero's journey, The Karate Kid movie